Jewelry bulky bracelet / Nor Afrina Natalia Hasanal Ali - Hasanal Ali, Nor Afrina Natalia (2022)
Jewelry product which is Big Bracelet inspired by Malaysian Batik. Malaysian Batik known as one of Malaysian Heritage or culture. Batik an age-old craft that has been practised for countless years. Countries like Indonesia, the Middle East, Thailand, Africa, Malaysia, India, China, the Philippines, and others all practise it. Through design process Malaysian batik motif developed into jewelry product.